2018
DOI: 10.1155/2018/9726950
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous CDKL5 Knockout Female Mice Are a Valuable Animal Model for CDKL5 Disorder

Abstract: CDKL5 disorder is a severe neurodevelopmental disorder caused by mutations in the X-linked CDKL5 (cyclin-dependent kinase-like five) gene. CDKL5 disorder primarily affects girls and is characterized by early-onset epileptic seizures, gross motor impairment, intellectual disability, and autistic features. Although all CDKL5 female patients are heterozygous, the most valid disease-related model, the heterozygous female Cdkl5 knockout (Cdkl5 +/−) mouse, has been little characterized. The lack of detailed behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 62 publications
(124 reference statements)
6
77
0
Order By: Relevance
“…In addition, Cdkl5 -/y transgenic mice were used as a model for the cyclin-dependent kinase-like 5 (Cdkl5) deficiency disorder (CDD) caused by loss of function mutation in the X-linked Cdkl5. Both diseases are associated with abnormalities in the neuronal architecture in hippocampal and cortical neurons, including simpler dendritic arbors and reduced dendritic lengths starting already at very early stages during development [16,17,36] [21,22,37,38].…”
Section: Fingolimod-phosphate (Fty720-p) Completely Rescues the Neurimentioning
confidence: 99%
“…In addition, Cdkl5 -/y transgenic mice were used as a model for the cyclin-dependent kinase-like 5 (Cdkl5) deficiency disorder (CDD) caused by loss of function mutation in the X-linked Cdkl5. Both diseases are associated with abnormalities in the neuronal architecture in hippocampal and cortical neurons, including simpler dendritic arbors and reduced dendritic lengths starting already at very early stages during development [16,17,36] [21,22,37,38].…”
Section: Fingolimod-phosphate (Fty720-p) Completely Rescues the Neurimentioning
confidence: 99%
“…CDKL5 mutations have been found in CDD patients and in subjects with neurodevelopmental disorders including ASD, atypical Rett syndrome, and early infantile epileptic encephalopathy. Mice lacking CDKL5 display a broad spectrum of behavioral abnormalities, including impaired learning and memory and autisticlike phenotypes (31)(32)(33).…”
Section: Significancementioning
confidence: 99%
“…Recent studies indicated the role of Mecp2 in social deficits [Ito-Ishida, Ure, Chen, Swann, & Zoghbi, 2015], communication deficits, abnormalities in social interactions, and stereotyped behaviors [Wohr et al, 2015]. Mice lacking CDKL5 displays a broad spectrum of behavioral abnormalities, including impaired learning and memory and autisticlike phenotypes [Amendola et al, 2014;Fuchs et al, 2018;Okuda et al, 2018]. Mutations in Ash2l and Mef2c genes have been identified in human neurological diseases, including ASDs.…”
Section: Introductionmentioning
confidence: 99%